Karakteristik Fisikokimia Tepung Tulang Ikan Kakap Merah (Lutjanus sp - Kaliky, Nurainy; Lessy, AbuBakar; Rieuwpassa, Fredy; Kaya, Adrianus Orias; Mailoa, Meigy Nelce; Sormin, Raja Bonan Dolok (INSTITUT AGAMA ISLAM NEGERI AMBON, 2024)
One of Maluku's marine biological resources is red snapper (Lutjanus sp). Red snapper is a type of demersal fish that has white flesh and has economic value. The flesh of this fish is very popular, while the bones of the snapper are thrown away. To increase the economic value of fish bones, the fish bone product was diversified into fish bone meal. This research aims to obtain values of the physicochemical and organoleptic characteristics of red snapper bone meal. The research method used was quantitative descriptive with a laboratory experimental approach with a single treatment repeated three times. The research test parameters are proximate analysis, calcium, kamba density, whiteness, absorbency and organoleptic parameters (color and texture). The results showed that fish bone meal contains water content (6.64%), calcium (44.824%), ash (59.93%), protein (6.27%), kamba density (0.098g/ml), white degree (72.33%), water absorption (129.90%), texture (3.60) and color (4.27). Keywords: Calcium, Ash, Kamba Density, Texture, Color